Uncovering Alumni Perspectives: A Cluster Analysis of University Satisfaction - Martinez-Hague, Paloma; Lau, Milos; Macarachvili, Andres; Caldas, Geraldine (ICAReAlumni Conference Proceedings, 2023)
In the cluster analysis "We obtained five clusters with a good measure of cohesion , silhouette , and separation as a result of the application of the two stage technique , using six variables: sex, specialty , current employment status, and the three items of the perception of satisfaction It means that the resulting clusters have a good " separation between them and high cohesion within each one. In short, their quality ensures that there would be no overlap between the clusters."